2020
DOI: 10.21203/rs.3.rs-46043/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Association between Frequency of Eating Out with Overweight and Obesity Among Children Aged 6-17 in China: A National Cross-Sectional Study

Abstract: Background: In parallel with the increased prevalence of childhood overweight and obesity, the rate of eating out in China has increased dramatically in recent years. The purpose of the study was to explore the association between frequency of eating out with overweight and obesity among Chinese children.Methods: The representative sample of Chinese children aged 6-17 years (7685 boys; 7576 girls) was recruited from Chinese National Nutrition and Health Survey (CNNHS) in 2010-2012. Frequency of eating out was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…18 Moreover, the popularity of the Western diet may be another driving factor as it is rich in sugary desserts, refined grains, high-fat, highprotein dairy products and high-sugar beverages, 9,19 which are common in some developed countries and are appearing more frequently in developing countries. [20][21][22][23] Several dietary intervention trials demonstrate that a low glycaemic load diet, and omega-3 fatty acid and c-linoleic acid supplementation can improve various symptoms in patients with acne vulgaris, including the reduction in average counts of inflammatory lesions and sebum activity. [24][25][26][27] We found that the increase of burden rate was more pronounced in countries with lower baseline burdens, particularly in countries where the ASPR of acne vulgaris in 1990 was lower than 30 per 1000 people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Moreover, the popularity of the Western diet may be another driving factor as it is rich in sugary desserts, refined grains, high-fat, highprotein dairy products and high-sugar beverages, 9,19 which are common in some developed countries and are appearing more frequently in developing countries. [20][21][22][23] Several dietary intervention trials demonstrate that a low glycaemic load diet, and omega-3 fatty acid and c-linoleic acid supplementation can improve various symptoms in patients with acne vulgaris, including the reduction in average counts of inflammatory lesions and sebum activity. [24][25][26][27] We found that the increase of burden rate was more pronounced in countries with lower baseline burdens, particularly in countries where the ASPR of acne vulgaris in 1990 was lower than 30 per 1000 people.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review calculated a pooled odds ratio of 2·36 (95% CI 1·97–2·83) for patients who were overweight/obese with reference to normal/underweight, 17 which partly explained the increasing burden, as the global age‐standardized prevalence of obesity increased from 0·7% in 1975 to 5·6% in 2016 in girls, and from 0·9% in 1975 to 7·8% in 2016 in boys 18 . Moreover, the popularity of the Western diet may be another driving factor as it is rich in sugary desserts, refined grains, high‐fat, high‐protein dairy products and high‐sugar beverages, 9,19 which are common in some developed countries and are appearing more frequently in developing countries 20–23 . Several dietary intervention trials demonstrate that a low glycaemic load diet, and omega‐3 fatty acid and γ‐linoleic acid supplementation can improve various symptoms in patients with acne vulgaris, including the reduction in average counts of inflammatory lesions and sebum activity 24–27 .…”
Section: Discussionmentioning
confidence: 99%